Students' Reflections on the Use of the Zoom Video Conferencing Technology for Online Learning at a South African University - Mpungose, Cedric B. (International Journal of African Higher Education, 2021)
The majority of universities in South Africa offer face-to-face lectures, resulting in the neglect of online lectures, although learning management systems (LMS) have been adopted and are capable of supporting online learning (e-learning). The coronavirus pandemic (COVID-19) forced universities to move fully online and to adopt Video Conferencing Technologies (VCT) to supplement LMS for e-learning. However, most students confront challenges related to a digital divide, raising the question of whether universities are able to address these effectively. This study explored students’ reflections on the use of the Zoom VCT for e-learning at a South African university. An interpretive qualitative case study was conducted, with data generated using emailed reflective activities and Zoom focus group discussions with 26 students in a curriculum studies programme. The framework of connectivism was employed and the data were thematically analysed. The study found that Internet access was a major challenge. While most students enjoyed synchronous Zoom discussions, they were unable to use other Zoom functions for effective engagement. It is thus recommended that the university should develop an e-learning policy and provide the necessary resources and training to students in order to ensure fitness for purpose. Key words: students’ reflections, Zoom VCT, e-learning, face-to-face, curriculum, university